2014
DOI: 10.1111/ssqu.12107
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Concern Over Time: Evidence from the Longitudinal Analysis of a British Cohort Study from 1991 to 2008*

Abstract: Objective. We examined whether and how levels of environmental concern (EC) changed over time in the United Kingdom, from 1991Kingdom, from to 2008Kingdom, from -2009, as well as how EC relates to socioeconomic characteristics across this same timeframe. Methods. Using item response theory models on the last three sweeps of the British National Child Development Study 1958, we evaluated a measure of EC. Then, using latent growth curve models (LGCMs) we estimated the pattern of change for EC across time. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
(41 reference statements)
2
5
0
Order By: Relevance
“…A longitudinal UK study found that individuals who vote for the Conservative Party are less likely to be concerned about the environment. This study also reported increasing variance in environmental attitudes, suggesting higher levels of polarization on this issue dimension (Melis et al, 2014 The Times, the right leaning broadsheet newspapers, focus on reporting positive aspects of shale gas and hydraulic fracturing including energy security and the possibility for lower gas prices. The Independent and The Guardian, centre and left leaning broadsheet newspapers, focus on negative aspects of shale gas and hydraulic fracturing including the risk of drinking water contamination and earthquakes (Jaspal and Nerlich, 2014).…”
Section: Party Affiliationmentioning
confidence: 64%
“…A longitudinal UK study found that individuals who vote for the Conservative Party are less likely to be concerned about the environment. This study also reported increasing variance in environmental attitudes, suggesting higher levels of polarization on this issue dimension (Melis et al, 2014 The Times, the right leaning broadsheet newspapers, focus on reporting positive aspects of shale gas and hydraulic fracturing including energy security and the possibility for lower gas prices. The Independent and The Guardian, centre and left leaning broadsheet newspapers, focus on negative aspects of shale gas and hydraulic fracturing including the risk of drinking water contamination and earthquakes (Jaspal and Nerlich, 2014).…”
Section: Party Affiliationmentioning
confidence: 64%
“…On the other hand, years of education has also been found to have an inverse relationship with concern about climate change (e.g., Malka et al, 2009 ; Slimak and Dietz, 2006 ). Other studies, for instance, Melis et al ( 2014 ) and Rhead et al ( 2018 ) found that education level is not a significant predictor for environmental concern in the UK population once other factors are controlled for. This may partly be because the effects of education on concern about climate change tend to interact with those of political affiliation (Hamilton, 2011 ).…”
Section: Introductionmentioning
confidence: 93%
“…McEvoy ( 1972 ) attributed this to men having higher levels of education (at the time) and greater involvement in the community and political issues. Yet others found no significant effect of gender on environmental concern (e.g., Melis et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several large-scale value surveys show that citizens tend to attach great value to a healthy environment and that they consider environmental degradation to be an important problem (Melis, Elliot, & Shryane, 2014). Moreover, there appears to be a positive link between environmental concern and willingness to pay (WTP) for a clean environment (Pagiaslis and Krontalis, 2014).…”
Section: Tax Aversionmentioning
confidence: 99%